Influence of the wetting properties of polymeric adhesives on the mechanical behaviour of cork agglomerates - Teixeira, M. J.; Fernandes, A. C.; Saramago, B.; ROSA, M. E.; BORDADO, J. C. (JOURNAL OF ADHESION SCIENCE AND TECHNOLOGY, 1996)
A series of adhesives, polyurethane prepolymers with alkane chains of different functionalities, were used in the production of cork agglomerates. The polymeric structure varied from long, linear chains in adhesive M1 (14% isocyanate groups) to short, branched chains in adhesive M4 (30% isocyanate groups). The wetting properties of the adhesives were studied through surface tension and contact angle measurements of the polymeric liquids deposited on cork substrates. The mechanical behaviour of the cork agglomerates was studied through compression and three-point bending tests, and the agglomerate structure was analysed by scanning electron microscopy (SEM). The relationship between the structural and wetting characteristics of the adhesives and the mechanical properties of the agglomerates was investigated. The experimental results indicate that it is the work of adhesion for the adhesive/cork system, and not only the contact angle, which determines the mechanical resistance of the cork agglomerate.
The following values have no corresponding Zotero field: pub-location: PLANTIJNSTRAAT 2, P O BOX 9000, 2300 PA LEIDEN, NETHERLANDS publisher: BRILL ACADEMIC PUBLISHERS
Keywords: adhesives; cork agglometares; mechanical properties; WETTING